Development of HPLC analysis for the determination of retinol and alpha tocopherol in corn oil nanoemulsion lotion - Thongchai W. (2017)
In this study was to extract and analyses composition of corn oil and develop cosmetics from corn oil extract. A simple high performance liquid chromatographic procedure for the determination of retinol and alpha tocopherol from corn oil nanoemulsions was proposed. The preparation condition for nanoemulsions of corn oil by high pressure homogenization was investigated. It appeared that the appropriate number of homogenization cycle was 8 cycles under the pressure of 1,000 bars at 25°C for the formula which contained 40% of corn oil, 15% of the mixed surfactant between Tween 80 and Span 80. The droplet sizes of the corn oil nanoemulsions were found to be 115.5±0.6 nm. The HPLC method was developed and validated for various chromatographic conditions for simultaneous determination of retinol and alpha tocopherol in corn oil nanoemulsion. The sample was analyzed on an Inersil C8-3 (4.6 mm×150 mm), using methanol and water as mobile phase with gradient elution system and detected at 292 and 325 nm for alpha tocopherol and retinol, respectively by spectrophotometer. The flow rate was used at 1 mL min -1 to complete separation of both analyzes. Under the optimum conditions, retinol and alpha tocopherol could be determined within a concentration range of 5-40 μg mL -1 which can be expressed by the regression equation y = 57507x+136421 (r 2 = 0.9990) and y = 10434x+26394 (r 2 = 0.9980), respectively. The limit of detection and quantitation were found to be 0.063 and 0.192 μg mL -1 for retinol and 0.067 and 0.203 μg mL -1 for alpha tocopherol, respectively. The proposed method was applied to the determination of retinol and alpha tocopherol contents in corn oil nanoemulsions.